Sesquineolignans and Terpene-Sesquineolignans: Anti-Acetylcholinesterase Constituents from Illicium simonsii - Dong, Chuanfu; Liu, Lei; Li, Xiaonian; Guan, Zhengye; Luo, Huairong; Wang, Yifen (Planta Medica, 2013)
Chemical investigation of the aerial parts of Illicium simonsii resulted in the isolation of nine new compounds, simonsols A−E (1–5), simonsins A−B (7–8), terpene-sesquineolignans, clovanedunnianol (9), and p-menthadunnianol (10). Compound 5 was equilibrated with 7 as an inseparable mixture. The structures were elucidated by extensive NMR and MS analysis. Compounds 9, 10, and the mixture of 5 and 7 moderately inhibited acetylcholinesterase with IC50 values of 4.58 µM, 6.55 µM, and 10.34 µM, respectively.
Keywords: Illiciaceae; Illicium simonsii; sesquineolignans; terpene-sesquineolignans; anti-AChE activity